RECONSTRUCTION OF MATAN HADITH UNDERSTANDING ABOUT WOMEN POSITION IN HOUSEHOLD - Damanhuri Damanhuri (Jurnal Ilmiah Peuradeun, 2016)
Matan hadith understanding of the women position in the family, in variety of classical fiqh books, especially the discussion about morals and the rights and obligations of one's wife in the family, tend to give a low position for women compared to the husband position. The wife is represented as the super, perfect and completely able to be submissive and obedient in total, so it is quite narrow opportunities for her to get a fair life as the position of her husband's life. This study discuss the meaning and interpretation by using a contextual approach and rational. This study aims to provide a more comprehensive directive in the meaning of the text of the hadith and dismissed accusations that lead to less humane view of the treatment of women in the household as well as being a comparison of thought in understanding the hadith of the prophet.